Respuesta :
Answer:
u = - [tex]\frac{24}{7}[/tex]
Step-by-step explanation:
Given that u varies directly with v then the equation relating them is
u = kv ← k is the constant of variation
To find k use the condition u = 6 when v = - 7, thus
k = [tex]\frac{u}{v}[/tex] = [tex]\frac{6}{-7}[/tex] = - [tex]\frac{6}{7}[/tex]
u = - [tex]\frac{6}{7}[/tex] v ← equation of variation
When v = 4, then
u = - [tex]\frac{6}{7}[/tex] × 4 = - [tex]\frac{24}{7}[/tex]
Step-by-step explanation:
[tex]u \: directly \: v[/tex]
[tex]u = k \: v[/tex]
[tex]u = 6[/tex]
[tex]v = - 7[/tex]
putting in upper equation to get value of k
[tex]6 = - 7k[/tex]
[tex] \frac { - 6}{ 7} = k[/tex]
u when v=4
[tex]as \: u = kv[/tex]
[tex]u = \frac{ - 6}{7} \times 4[/tex]
[tex]u = \frac{ - 24}{7} [/tex]